Morfologia e funcionalidade da rede porosa de horizontes com e sem caráter coeso em solos de Tabuleiro Costeiro - Menezes, Ademir Silva (2016)
The knowledge on morphology and function of the pore network is important for the management of soils in the agriculture. Assuming that horizons with cohesive character have different porous network due to the large amount of small pores and especially for being horizontally oriented, the aim of this work was to compare the morphology, functionality and orientation of the pores in cohesive and non-cohesive horizons of clayey-sandy loam and sandy loam texture in coastal boards of Ceará state, Brazil. Samples of cohesive and non-cohesive horizons were collected from Argissolo Vermelho-Amarelo Distrófico típico (PVAd) and Argissolo Amarelo Eutrocoeso abrúptico (PAex) with preserved structure in horizontal and vertical positions. For micromorphometric analyzes, the samples were collected in cardboard box with dimensions of 0.12 x 0.07 x 0.04 m. Evaluations of particle size, bulk density, porosity, air permeability, average length of pores, retention curve, penetration resistance and micromorphometrics were made. It was considered a completely randomized design in a factorial 2 x 2 (cohesive Bt and Bt non-cohesive; two collection positions: horizontal and vertical) with seven replicates. The data were submitted to Shapiro-Wilk, F and Tukey tests, all with a 95% confidence interval. The density of the soil for Cohesive was statistically superior to non-cohesive in PVAd and PAex. The porosity in cohesive horizons was significantly lower than that observed for non-cohesive on both soils. The micropores of the cohesive horizon at different positions in PVAd do not differ significantly. It was concluded that horizons with cohesive character have different porous network as the morphology and functionality in the soil; the porous network of cohesive horizons is more efficient horizontally, with a predominance of rounded pores; the pores in the horizons with cohesive character are less functional than the horizons without cohesive character.